Obesity-Induced Tumor Necrosis Factor Alpha Suppresses In Vivo and In Vitro Retinoic Acid Synthesis and Fatty Acid Oxidation in Adipose Tissue. (7th June 2021) - Yu, Seok-Yeong; Liu, Zhenhua; Chung, Soonkyu; Kim, Young-Cheul
Abstract: Objectives: Obese adipose tissue (AT) is characterized by decreased fatty acid oxidation (FAO) and overexpression of tumor necrosis factor alpha (TNFα), a potent proinflammatory mediator of AT dysfunction and metabolic diseases. Several studies have shown that biosynthesis of retinoic acid (RA) from retinol (vitamin A) is suppressed in obese AT. RA has been identified as an agonist for peroxisome proliferator-activated receptor beta/delta (PPARβ/δ), a critical inducer of FAO. The present study aimed to identify a potential mediator of suppressing RA synthesis and thus metabolic dysregulation by (1) evaluating the role of TNFa in tissue RA synthesis and metabolism in vivo and (2) investigating the potential roles of all trans-RA (ATRA) against TNFa-induced AT dysfunction in vitro . We hypothesized that altered retinoid metabolism in obese AT leads to AT dysfunction by reducing PPARβ/δ expression in adipocytes and macrophages. Methods: Wild-type (WT) or TNFa knockout (KO) mice were fed a high-fat diet (HFD) or a low-fat diet (LFD) for 16 weeks. Selected serum biochemical parameters as well as expression of genes related to FAO and retinol metabolism were assessed by qPCR and Western Blot analysis. 3T3-L1 adipocytes and RAW264.7 macrophages were also employed to evaluate the effect of TNFa and ATRA on RA synthesis and pro-inflammatory responses. Results: We found that RA concentration was significantly attenuated in epididymal AT from HFD-fed TNFa KO group concomitant with the upregulation of genes for RA synthesis ( RDH10 & RALDH1 ) and PPARβ/δ compared to HFD-fed WT group. In 3T3-L1 adipocytes, TNFa treatment significantly inhibited RA synthesis from retinol and downregulated the expression of RDH10 & RALDH1 genes and FAO makers (PPARβ/δ protein and CPT1 mRNA). Furthermore, ATRA treatment significantly increased the expression of PPARβ/δ protein and CPT1 mRNA in TNFα-treated cells. In addition, ATRA significantly suppressed adipocyte-conditioned medium-induced inflammatory responses in RAW264.7 macrophages by increasing PPARβ/δ expression. Conclusions: These findings suggest that TNFα overexpressed in obesity mediates AT dysfunction by impairing RA synthesis and ATRA may confer protection against obesity-induced metabolic comorbidities. Funding Sources: This project was partially supported by the US Department of Agricultural Experiment Station (MAS00503).